“Aquele Abraço”: o discurso identitário cultural brasileiro que se abre para o mundo - Almeida Júnior, Jair de (2015)
It analysis the Brazilian and Lusophone cultural identity discourse through three-way path. First, it is emphasized that it was marked decisively by Portuguese culture, first of its interacting with Indian culture and then with the African culture. The culture of settlers of Brazil was eminently Catholic, a direct result of religious discourse and constituent medievalism that religion. The concept of "cornerstone" is employed for the role of Portuguese culture in the colonization, borrowed from the Christian Scriptures that apply to the Biblical Christ as the one who ruled in his life and teachings of Christianity. Similarly, in the construction of the Brazilian identity building, Portuguese culture is established as the main stone in its foundation, determining and giving basis to all that would follow its implementation in Brazil. The carnival, attachment to the monarchy and fears, seen today as "superstitions" in our society, they were constitutive medievalism of the cultural identity of the nation discourse, Portuguese heritage. The second way that is exploited to analyse the formation of the Brazilian cultural identity discourse is in the application of Heidegger's thought as a tool for understanding of the transition from religious to secular, the shift that occurred especially in the late nineteenth century to the twentieth. It will be highlighted his concepts of memory, Dasein, as well as Augustinian beata vita secularized in his philosophy. The importance of Heidegger is already on its path from youth Catholic militant to existentialist philosopher, highlighting the secularism that results from his writings in the process of building their own identity. The third way is linked to the discourse analysis by greimasian optics, in which will be perceived the essential interaction of religious discourse in the Brazilian life until the nineteenth century, when there is the great secular turn. This was due to pressure from various modernist ideas were beginning to operate a detachment of a secular identity, because until this moment, there was only eminently Catholic national identity. It demonstrates how the centrality of Virgin Mary invocations contributed to this, drawing to itself the religious identification of the country, paving the way for the Cristo Redentor, has assimilated the Rio’s landscape yet, became the great Brazilian cultural icon, with its original intent secularized to represent a prosperous and happy life, open to all peoples and all cultures.